Extreme Two‐Phase Cooling from Laser‐Etched Diamond and Conformal, Template‐Fabricated Microporous Copper. (4th October 2017) - Palko, James W.; Lee, Hyoungsoon; Zhang, Chi; Dusseault, Tom J.; Maitra, Tanmoy; Won, Yoonjin; Agonafer, Damena D.; Moss, Jess; Houshmand, Farzad; Rong, Guoguang; Wilbur, Joshua D.; Rockosi, Derrick; et al.
Abstract: This paper reports the first integration of laser‐etched polycrystalline diamond microchannels with template‐fabricated microporous copper for extreme convective boiling in a composite heat sink for power electronics and energy conversion. Diamond offers the highest thermal conductivity near room temperature, and enables aggressive heat spreading along triangular channel walls with 1:1 aspect ratio. Conformally coated porous copper with thickness 25 µm and 5 µm pore size optimizes fluid and heat transport for convective boiling within the diamond channels. Data reported here include 1280 W cm −2 of heat removal from 0.7 cm 2 surface area with temperature rise beyond fluid saturation less than 21 K, corresponding to 6.3 × 10 5 W m −2 K −1 . This heat sink has the potential to dissipate much larger localized heat loads with small temperature nonuniformity (5 kW cm −2 over 200 µm × 200 µm with <3 K temperature difference). A microfluidic manifold assures uniform distribution of liquid over the heat sink surface with negligible pumping power requirements (e.g., <1.4 × 10 −4 of the thermal power dissipated). This breakthrough integration of functional materials and the resulting experimental data set a very high bar for microfluidic heat removal. Abstract : Integration of laser‐etched polycrystalline diamond microchannels with template‐fabricated microporous copper allows extreme convective boiling. Diamond spreads heat through extended surfaces conformally coated with thin (25 µm) porous copper, which optimizes fluid and heat transport in boiling. The structure dissipates 1280 W cm −2 of heat from 0.7 cm 2 area with temperature rise beyond fluid saturation below 21 °C, corresponding to 6.3 × 10 5 W m −2 K −1 .